Figurative Meaning in Inaugural Speech of Joe Biden - Nenny Kartika Dewi; Sudirman Maca; Andi Tenri Abeng (Humaniora: Journal of Linguistics, Literature, and Education, 2021)
This study aimed to discover and explain the types, lexical meaning and contextual meaning of figurative languages used in Joe Biden’s Inaugural speech and this study is hoped to be utilized by further researcher. The data sources used in this study was the inaugural speech of Joe Biden. Inanalyzing the data, the writer used descriptive qualitative research method through semantic approach. Data were obtained by using the techniques of reading, noting, and analyzing. While inclassifying the data, the writer used Keraf’s theory of figurative language. In this study, the writeranalyzed the inaugural speech of Joe Biden in order to find and classify the figurative language and the meaning. The results of this study indicate that there were 13figurative language used by Joe Biden. There were 6 types figurative language found in the speech consists of six metonym, one synecdoche, two simile, one epithet, two metaphor and one allusion. There were 26 meanings of the data consists of13 contextual meanings of the data which the meanings based from the context where the language is used. And 13 lexical meanings of the data were the meanings found in online dictionary.